2021
DOI: 10.18805/lr-4357
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Pulses Productivity and Agronomic Opportunities for Enhancing Growth and Yield in Blackgram [Vigna mungo (L.) Hepper]: A Review

Abstract: Background: Blackgram is an important pulse crop. The productivity of crops can be enhanced through various input management and selection of suitable genotypes for different systems and seasons of cultivation. An attempt was made to gather published information on crop management for yield maximisation. Methods: This work was done at Department of Agronomy, Agricultural College and Research Institute, Tamil Nadu Agricultural University, Madurai - 625104, Tamil Nadu, India. A systematic cum integrative review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…4). Similar results were obtained by Sunandini and Devi [5], Shyamsundar G.,et al, [3], Mohiuddin M. et al, [4] and Swaminathan C.,et al, [6].…”
Section: Cost Of Cultivation Of Black Gram Among Sample Farmers Of Fposupporting
confidence: 86%
“…4). Similar results were obtained by Sunandini and Devi [5], Shyamsundar G.,et al, [3], Mohiuddin M. et al, [4] and Swaminathan C.,et al, [6].…”
Section: Cost Of Cultivation Of Black Gram Among Sample Farmers Of Fposupporting
confidence: 86%
“…Similarly, iron, copper and manganese content also increase in response to different treatment combinations (Table 2) (Husain et al, 2011;Yadav et al, 2017). It observed that the favorable effect on soil as well as on plant was due to positive soil micro climate regime in soil and its effect on both plant and soil in terms of increase in the macro and micro nutrient concentration (Gosh and Das 2011;Swaminathan et al, 2020). Effect of Integrated Nutrient Management on Quality, Yield, Nutrient Content and Uptake of Black Gram (Vigna mungo L.) in... Effect of Integrated Nutrient Management on Quality, Yield, Nutrient Content and Uptake of Black Gram (Vigna mungo L.) in...…”
Section: Nutrient Content Of Blackgrammentioning
confidence: 97%
“…India is the world's largest producer as well as consumer of black gram [1]. In India, black gram is third most important pulse crop grown under rainfed, rice fallow, irrigated conditions and during kharif, rabi and summer seasons, which matures in 90-100 days and it enriches soil with nitrogen [2]. Cultivating blackgram requires well-drained soil and a warm climate, with temperatures ranging between 25 to 35 degrees Celsius.…”
Section: Introductionmentioning
confidence: 99%